Voltar, contar e lembrar de Gangan: por uma arqueologia griótica afrodecolonial em Mana, Guiana - Gabby Hartemann (2019)
This MA thesis constitutes a critical effort from the knowledge mode that is archaeology. Based on an openly afrodecolonial perspective, the research proposes theoretical and practical shifts from the western and modern forms with which archaeology has been made, with a particular emphasis for the question of otherness. The notion of "return", both to Mana, ancestral land of the researcher, and to afrocentered world-perceptions, constitutes the starting point for these reflections. Therefore, the concepts of ancestrality, memory and orality are activated to construct other possibilities for archaeology that are less colonialistic and less violent, such as the perspective of griotic archaeology proposed in this thesis